Powerful PowerPoint / Tuan Sarifah Aini Syed Ahmad - Syed Ahmad, Tuan Sarifah Aini (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2019)
I believe that most educators are familiar with PowerPoint. It is one of the Microsoft Office applications that is available in all computers. PowerPoint is commonly used for preparing presentation slides for teaching. Educators usually include text, graphics, sounds and background music or to include slide transitions and slide animations in order to make their slides more appealing to students.